Phenotypic and genome-wide analysis of an antibiotic-resistant small colony variant (SCV) of Pseudomonas aeruginosa. - Qing Wei; Saeed Tarighi; Andreas Dötsch; Susanne Häussler; Mathias Müsken; Victoria J Wright; Miguel Cámara; Paul Williams; Steven Haenen; Bart Boerjan; Annelies Bogaerts; Evy Vierstraete; et al. (PLoS ONE)
Background Small colony variants (SCVs) are slow-growing bacteria, which often show increased resistance to antibiotics and cause latent or recurrent infections. It is therefore important to understand the mechanisms at the basis of this phenotypic switch. Methodology/principal findings One SCV (termed PAO-SCV) was isolated, showing high resistance to gentamicin and to the cephalosporine cefotaxime. PAO-SCV was prone to reversion as evidenced by emergence of large colonies with a frequency of 10(-5) on media without antibiotics while it was stably maintained in presence of gentamicin. PAO-SCV showed a delayed growth, defective motility, and strongly reduced levels of the quorum sensing Pseudomonas quinolone signal (PQS). Whole genome expression analysis further suggested a multi-layered antibiotic resistance mechanism, including simultaneous over-expression of two drug efflux pumps (MexAB-OprM, MexXY-OprM), the LPS modification operon arnBCADTEF, and the PhoP-PhoQ two-component system. Conversely, the genes for the synthesis of PQS were strongly down-regulated in PAO-SCV. Finally, genomic analysis revealed the presence of mutations in phoP and phoQ genes as well as in the mexZ gene encoding a repressor of the mexXY and mexAB-oprM genes. Only one mutation occurred only in REV, at nucleotide 1020 of the tufA gene, a paralog of tufB, both encoding the elongation factor Tu, causing a change of the rarely used aspartic acid codon GAU to the more common GAC, possibly causing an increase of tufA mRNA translation. High expression of phoP and phoQ was confirmed for the SCV variant while the revertant showed expression levels reduced to wild-type levels. Conclusions By combining data coming from phenotypic, gene expression and proteome analysis, we could demonstrate that resistance to aminoglycosides in one SCV mutant is multifactorial including overexpression of efflux mechanisms, LPS modification and is accompanied by a drastic down-regulation of the Pseudomonas quinolone signal quorum sensing system.